Expectations and patients' experiences of obesity prior to bariatric surgery: a qualitative study. Issue 2 (8th February 2016) - Homer, Catherine Verity; Tod, Angela Mary; Thompson, Andrew R; Allmark, Peter; Goyder, Elizabeth
Abstract : Objectives: This study aimed to understand the experiences and expectations of people seeking bariatric surgery in England and identify implications for behavioural and self-management interventions. Design: A qualitative study using modified photovoice methods, triangulating photography with semistructured indepth interviews analysed using framework techniques. Setting: Areas served by two bariatric surgery multidisciplinary teams in the north of England. Participants: 18 adults (14 women and 4 men) who accepted for bariatric surgery, and were aged between 30 and 61 years. Participants were recruited through hospital-based tier 4 bariatric surgery multidisciplinary teams. Results: The experiences of participants indicates the nature and extent of the burden of obesity. Problems included stigmatisation, shame, poor health, physical function and reliance on medications. Participants expected surgery to result in major physical and psychological improvement. They described how this expectation was rooted in their experiences of stigma and shame. These feelings were reinforced by previous unsuccessful weight loss attempts. Participants expected extreme and sometimes unrealistic levels of sustained weight loss, as well as improvements to physical and mental health. The overall desire and expectation of bariatric surgery was of 'normality'. Participants had received previous support from clinicians and in weight management services. However, they reported that their expectations of surgery had not been reviewed by services, and expectations appeared to be unrealistic. Likewise, their experience of stigmatisation had not been addressed. Conclusions: The unrealistic expectations identified here may negatively affect postoperative outcomes. The findings indicate the importance of services addressing feelings of shame and stigmatisation, and modifying patient's expectations and goals for the postoperative period.